Designing A Catalog of UMKM Metal Crafts in Fancy Copper as A Branding and Marketing Media - Fathurrahman, Ahmad (Universitas Sahid Surakarta, 2024)
: Promotion plays a crucial role in enhancing sales in the Micro, Small, and Medium Enterprises (MSME) sector. One proven method of promotion that effectively influences consumer purchasing decisions is through the use of product catalogs, whether in print or digital form. Catalogs not only serve as sources of product information but also function as tools to promote the unique features of the offered products. In this context, this Community Service Program (KKN) is dedicated to creating product catalogs for Fancy Copper, an MSME. The objective of this program is to introduce copper and brass products through both print and digital catalogs, with the hope of boosting product sales. The KKN program activities consist of four stages: problem analysis through interviews and discussions, data collection and product photo capture, design of the product catalog, and the composition of catalog content. Evaluation results indicate that the use of product catalogs successfully captures consumer interest and has a positive impact on sales growth